ANALISIS PENDIDIKAN KEWIRAUSAHAAN DAN LATAR BELAKANG KELUARGA TERHADAP KEINGINAN BERWIRAUSAHA (studi pada Generasi Z di Jakarta) - Mawaddatul Ulya (JURNAL MUHAMMADIYAH MANAJEMEN BISNIS, 2025)
Generation Z represents a unique demographic group, growing up in the digital era and facing complex employment challenges, particularly in urban areas such as Jakarta. The high rate of educated unemployment and the mismatch between the education system and industry needs demand a new approach to fostering entrepreneurial intention. This study aims to analyze the influence of entrepreneurship education and family background on the entrepreneurial intention of Generation Z. A review of the literature reveals that entrepreneurship education delivered actively, experientially, and encompassing dimensions of knowledge, skills, and entrepreneurial mindset has a significant impact on building motivation and readiness for entrepreneurship. On the other hand, the family, as the first social environment, also plays a crucial role through emotional support, role modeling, and facilitative assistance that can strengthen self-confidence and interest in exploring the business world. The situation in Jakarta highlights the urgency of synergy between education and family as a supportive ecosystem to nurture a generation that is independent, innovative, and capable of creating new employment opportunities. Keywords: Generation Z, family background, entrepreneurial intention.